Staining of wood veneers with anti-UV property using the natural dye extracted from Dalbergia cohinchinensis. (15th February 2021) - Zhu, Tao; Sheng, Jiale; Chen, Jiabao; Ren, Kai; Wu, Zhenzeng; Wu, Hui; Li, Jian; Lin, Jinguo
Abstract: In present study, a recyclable and environmentally friendly dyeing method through using extractives from Dalbergia cohinchinensis residues without any mordant as natural dye (ND) was studied with the objective of improving anti-UV property of the dyed wood. The dyeing mechanism was explored and the anti-UV property of ND dyed wood was evaluated. The results indicated that total color difference was negative correlate with O/C ratio of dyed wood surface (R 2  = 0.9578). After UV irradiation treatment, the total color difference change, the color change rate and reflectance curves variation of ND dyed wood exhibited apparently lesser. Also, the color intensity of ND dyed wood decreased slighter (3.22%) compared to that of acid red dyed wood (40.39%) irradiated at shorter UV wavelength (313 nm). The dye coating spontaneously depositing on the surface of wood fiber imparted anti-UV property of ND dyed wood, which can be ascribed to reduction of photo-discoloration and mitigation of lignin degradation by ND layer absorbing and reflecting UV lights effectively. In addition, the staining method was shown to be a recyclable and eco-friendly scenario by SWOT analysis, which can be employed as potential alternatives of synthetic dyestuff in wood dyeing industry to meet cleaner production demand. Graphical abstract: Image 1 Highlights: Dalbergia cohinchinensis extracts were used as natural dye with anti-UV property. The natural dye mitigated the photo-discoloration and lignin degradation of wood. The dyeing method was a recyclable and eco-friendly scenario.